2023
DOI: 10.3390/pharmaceutics15030952
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Cell-Penetrating Peptides for Efficient and Selective In Vivo Expression of mRNA in Spleen Tissue

Abstract: mRNA-based therapeutics are presently one of the nucleic acid-based therapeutics with a high potential for extraordinary success as preventive vaccines. Current applications with mRNA therapeutics rely on lipid nanoparticle (LNP) mediated delivery of nucleic acids. In order to achieve the transition from preventive to therapeutic vaccines, there is a challenge of delivering the mRNA into non-hepatic tissues, especially into lymphoid tissues such as the spleen and lymph nodes. In this work, we characterize new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Porosk et al introduced new CPP variants, NF424 and NF436, which preferentially targeted mRNA delivery to the spleen following a single intravenous injection without requiring additional active targeting mechanisms. 109 3.5. Inorganic NPs.…”
Section: Nps-based Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porosk et al introduced new CPP variants, NF424 and NF436, which preferentially targeted mRNA delivery to the spleen following a single intravenous injection without requiring additional active targeting mechanisms. 109 3.5. Inorganic NPs.…”
Section: Nps-based Delivery Systemsmentioning
confidence: 99%
“…Despite relatively slow progress in delivering mRNA in vivo, CPPs hold promise in overcoming the challenge of mRNA delivery to nonhepatic tissues, a constraint typically seen with LNPs, which predominantly accumulate in the liver. Porosk et al introduced new CPP variants, NF424 and NF436, which preferentially targeted mRNA delivery to the spleen following a single intravenous injection without requiring additional active targeting mechanisms …”
Section: Nps-based Delivery Systemsmentioning
confidence: 99%
“…Therefore, the key to enabling the growth of this approach is the development of efficient vectors that complex, deliver and release mRNA into the cytosol. Most mRNA transfection systems are based on the use of lipid nanoparticles (LNPs) [8,9], although some recent publications also describe the use of cellpenetrating peptides (CPPs) as delivery vehicle for mRNA [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies reported CPP-mediated in vivo mRNA delivery [16]. For in vivo mRNA delivery studies, CPPs have been chemically modified or mainly utilized as a component of hybrid materials for carriers [17][18][19]. In addition, most of the previously employed CPPs for mRNA delivery have sequences derived from non-human organisms or modified from human protein sequences [13].…”
Section: Introductionmentioning
confidence: 99%